AROMATHERAPY CANDLE FORMULATION USING GRAPEFRUIT ESSENTIAL OIL WITH PATCHOULI ESSENTIAL OIL FIXATIVE - Ahmad, Ilham; Nur Asisah Ayu; Sushanti, Gusni; Muhtar, Imran (Journal of Agriculture, 2022)
The aim of this study was to obtain the best color formulation of aromatherapy candles using grapefruit oil with patchouli essential oil fixative and to analyze the business feasibility of grapefruit aromatherapy candles. This research was conducted from June to August 2021 in the quality testing laboratory for the Agroindustry study program, Pangkep State Agricultural Polytechnic. This research was conducted using an experimental method with two stages, namely; first, making aromatherapy candles which aims to get the best color concentration in aromatherapy candles with a hedonic test, after the hedonic test with the best color will proceed to further research, namely the stage of selecting the aromatherapy candle aroma of grapefruit essential oil as a binder added with patchouli oil. Business continuity analysis is carried out by looking for investment costs, variable costs, profits, production Break Even Point (BEP), price Break Even Point (BEP), Benefit Cost Ratio (BCR), and pay back period. The results showed that the best color formulation of aromatherapy candles was in the A3 treatment with a color concentration of 1.5% with an average of 3.6. The best aromatherapy candle formulation was in treatment B3 with a concentration of 2.5% grapefruit oil and 0.25% patchouli oil fixative with an average hedonic test result of 4.36. The best formulation of the effect of aromatherapy candles was in treatment B3 with a concentration of 2.5% grapefruit oil and 0.25% patchouli oil fixative with an average organoleptic test result of 6.52 and 80% of the panelists felt relaxed, comfortable, fresh and somewhat refreshed. The results of the Benefit Cost Ratio (BCR) calculation analysis in the aromatherapy business with a BCR value of 1.11 indicate that this business is feasible to develop.